(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2024)
Tropical dry forest ecosystems are threatened by climate change; they manage complex spatial and structural dynamics that affect both terrestrial and aquatic biological communities, such as macroinvertebrates, which are important in the adequate flow of nutrients and ecological stability of ecosystems. The present investigation lasted eight months (November 2021 – June 2022), contemplating climatic seasons of greater and lesser precipitation where the proportion of individuals was quantified considering the nature of the tropical dry forest, especially its effect on physicochemical variables. Methodologically, in the field phase, biological samples were collected, and hydrological and physicochemical data were recorded at five sampling stations. Descriptive statistics, diversity indices and multivariate methods were used for the analyses. Five phyla, six classes, 16 orders, 47 families and 62 genera were recorded, with Rhagovelia, Tricorythodes and Farrodes being the most representative. It was observed that variables such as total suspended solids, conductivity and water temperature influenced the macroinvertebrate community to a greater extent, which influenced a greater representativeness of tolerant individuals but characteristic of good quality waters, likewise the coefficients of variation demonstrated to have a lower relationship between macroinvertebrates and precipitation seasons.